Socio-demographic profile of patients with sarcoidosis vis-à-vis tuberculosis - Gupta, Dheeraj; Vinay, N; Agarwal, R.; Agarwal, A. N. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Background: Sarcoidosis and tuberculosis closely resemble each other and Mycobacterium tuberculosis has been implicated as a causative agent for sarcoidosis. Herein we explore the socio-demographic features of patients with sarcoidosis vis-a-vis tuberculosis. Methodology: In a prospective case-control design, we studied hundred patients each of newly diagnosed sarcoidosis, bacteriologically confirmed pulmonary tuberculosis and healthy controls. Socio-demographic profile was recorded on a standardized questionnaire. Information about tobacco smoking, exposure to environmental tobacco smoke (ETS) and cooking fuels was also collected. Various parameters were compared among the three groups. Results: Compared to tuberculosis, patients with sarcoidosis were elder, had better body mass index (BMI), higher urban residence (OR 2.19, 95% CI: 1.02-4.69), were better educated (ORs 8.50 to 74.25 for different categories), had higher per capita income (OR 13.33; 95% CI: 6.79-26.19) and belonged to better overall socio-economic status (SES) (ORs 8.57-195.0 for different categories). All these differences were also significant when sarcoidosis patients were compared to healthy controls albeit to a lesser degree. Tobacco smoking, ETS exposure and use of fossil/biomass fuels for cooking were more commonly seen in TB patients. In the multivariate analysis, as compared to TB or controls, sarcoidosis patients had higher odds for a better SES after adjusting for age, gender, BMI, religion, smoking, ETS exposure and cooking fuel. Conclusions: Patients with sarcoidosis are likely to be better educated and more affluent compared to those with tuberculosis and healthy controls and this can be useful in clinical differential diagnosis of the two conditions in populations with high prevalence of TB.